Sell the rumour, buy the fact?. (21st August 2012) - Marshall, Ben R.; Visaltanachoti, Nuttawat; Cooper, Genevieve
Abstract We document a high‐profile instance of mispricing that is puzzling given the gradual information diffusion hypothesis and the lack of obvious limits to arbitrage. An internet search in 2008 led to a story about United Airlines' 2002 bankruptcy being re‐released as 'news'. This resulted in United Airlines losing 73 per cent of its value and caused a 4.2 billion decline in the value of airline stocks and United Airlines suppliers. The incorrect bankruptcy 'news' was quickly retracted, which led to a rebound in other airline and supplier firms, but the stock price of United Airlines was adversely affected for 4 days.